Realidad Virtual Como Apoyo al Desarrollo de Habilidades No Técnicas en Profesionales de la Salud - Benavides, Christian O.; Peña, Samuel Antonio (KnE Engineering, 2018)
In recent years research has been done on how to gain non-technical skills, as one of the most influential factors in the daily work activities of the human being; This deficiency manifests itself more frequently in people of small age and with little professional experience, causing different negative effects on the psychological behaviors (cognitive, emotional, etc.), damaging their personal, familiar and work well-being. However, this factor is often developed with repetition in high workload scenarios, such as medical or hospital settings, and especially in areas of high labor demand and with a higher stress index such as the intensive care unit (ICU) and the emergency department Hospitals, which are places where the medical staff is exposed to provide a high quality personalized attention, under the pressure of the patient, relatives, directors and administrative of the hospitals, often provoking the alteration of their capacities or psychological factors At the time of providing the service and maintaining patient safety. Thus the proposal of the following research is to support the health professionals to gain non-technical skills through virtual reality to control adverse situations of the environment without harming the safety of the patient. Keywords: Virtual Reality, Human Machine Interaction, Medical Organizational Environment, Non-technical Skills